The life of Leonardo da Vinci - Hodge, Susie, 1960- (Columbus, OH : School Specialty Pub., 2006)
Looks at the life of Leonardo da Vinci, a fifteenth-century man who is known for his achievements as an artist, inventor, scientist, military engineer, philosopher, botanist, and mathematician. Presented in graphic novel form.
Includes index.
3.7
3-6
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Comic books, strips, etc. -- Juvenile literature; Artists -- Italy -- Biography -- Comic books, strips, etc. -- Juvenile literature; Scientists -- Italy -- Biography -- Comic books, strips, etc. -- Juvenile literature; Leonardo, -- da Vinci, -- 1452-1519 -- Cartoons and comics; Artists -- Cartoons and comics; Scientists -- Cartoons and comics; Cartoons and comics; Leonardo, -- da Vinci, -- 1452-1519 -- Comic books, strips, etc; Artists -- Italy -- Biography -- Comic books, strips, etc; Scientists -- Italy -- Biography -- Comic books, strips, etc; Comic books, strips, etc